Implementation of the Election Supervisory Agency’s (Bawaslu) Authority in Resolving Process Disputes in the 2024 Elections: A Case Study of Bawaslu East Lombok Regency - Puspitasari, Ema; Asmara, M. Galang; Purnomo, Chrisdianto Eko (Lex Journal : Kajian Hukum dan Keadilan, 2025)
This study aims to determine the implementation of the authority of the East Lombok Regency Election Supervisory Agency (Bawaslu) in resolving process disputes in the 2024 Election and the obstacles faced by the East Lombok Regency Bawaslu in resolving election process disputes. This research was conducted juridically and empirically. The approach taken is a statutory approach and a legal sociological approach. Based on the results of the research it is concluded: First, Bawaslu of East Lombok Regency has exercised its authority in receiving, examining, mediating or adjudicating, and deciding the settlement of disputes over the electoral process in the district/city by Law Number 7 of 2017 concerning General Elections and Regulation of the General Election Supervisory Board of the Republic of Indonesia Number 9 of 2022 concerning Procedures for Resolving General Election Process Disputes. However, because this institution holds two functions, the author feels that the settlement of disputes over the electoral process carried out by the Bawaslu East Lombok Regency is not optimal. Second, the obstacles faced by Bawaslu of East Lombok Regency in resolving disputes over the electoral process are: a. When submitting a dispute application, the applicant applies on the last day of the deadline for applying; b. The completion time for giving a decision is too short; c. Absence of the Applicant and Respondent Parties; d. Lack of human resources because not all commissioners have the authority to submit the dispute; e. lack of budget to prepare the administration of dispute resolution. The author suggests that Bawaslu of East Lombok Regency in exercising the authority to receive, examine, mediate, or adjudicate, and decide on the settlement of disputes over the election process must be by the applicable laws and regulations and must be carried out optimally. Improve the quality of human resources by holding mediation and adjudication training regularly to support the process of enforcing dispute resolution processes properly. In addition, the East Lombok Regency Bawaslu also submitted an additional budget to the Central Government through the Provincial Bawaslu.